2014
DOI: 10.1513/annalsats.201403-105aw
|View full text |Cite
|
Sign up to set email alerts
|

Airway Fibrinogenolysis and the Initiation of Allergic Inflammation

Abstract: The past 15 years of allergic disease research have produced extraordinary improvements in our understanding of the pathogenesis of airway allergic diseases such as asthma. Whereas it was previously viewed as largely an immunoglobulin E-mediated process, the gradual recognition that T cells, especially Type 2 T helper (Th2) cells and Th17 cells, play a major role in asthma and related afflictions has inspired clinical trials targeting cytokine-based inflammatory pathways that show great promise. What has yet t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…43 Fibrinogen cleavage products act as TLR4 ligands, enhancing innate immune response. 44 For instance, fibrinogen cleavage products can bind Toll like receptor 4 (TLR4), priming innate immune and airway epithelial cell response to IL-13, with downstream triggering of airway inflammation. 45 Two of the metabolites with altered levels in current asthmatics, taurocholate and biliverdin, are bile constituents.…”
Section: Discussionmentioning
confidence: 99%
“…43 Fibrinogen cleavage products act as TLR4 ligands, enhancing innate immune response. 44 For instance, fibrinogen cleavage products can bind Toll like receptor 4 (TLR4), priming innate immune and airway epithelial cell response to IL-13, with downstream triggering of airway inflammation. 45 Two of the metabolites with altered levels in current asthmatics, taurocholate and biliverdin, are bile constituents.…”
Section: Discussionmentioning
confidence: 99%
“…This is speculated to impact on development and progression of diabetes‐related vasculopathy. It is likely that dissolution of fibrin clots in other thrombotic or inflammatory disease states, such as asthma or colitis , might be modulated by integration of complement components into the clots and that targeting this step may be of value therapeutically.…”
Section: Cross‐talkmentioning
confidence: 99%
“…Previous studies have shown the expression of fibrinogen-binding proteins on the surface of conidia of A. fumigatus which promote binding to fibrinogen and host tissue [40,47]. The release of fungal proteases during infection has been reported to result in fibrinogen cleaving and activation of the TLR4 signaling pathway through binding of fibrinogen cleavage products [48][49][50]. The airway protease activity promoted by A. fumigatus initiates both allergic airway disease and antifungal immunity [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The release of fungal proteases during infection has been reported to result in fibrinogen cleaving and activation of the TLR4 signaling pathway through binding of fibrinogen cleavage products [ 48 50 ]. The airway protease activity promoted by A. fumigatus initiates both allergic airway disease and antifungal immunity [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%